Investigation of fracture parameters of self-compacting concrete produced with marble powder by peak-load method - Alyamac, Kursat Esat; Ince, Ragip (International Committee of the SCMT conferences, 2013)
Fracture parameters are among the most important characteristics of hardened concrete. In this study, SCC was investigated via the two-parameter fracture model (peak-load method) which needs two fracture parameters namely: the critical stress intensity factor KIC s and the critical crack mouth opening displacement CTODc to characterize failure of concrete structures. In SCC mix, different marble powders were used as powder materials. Marble powder is a new material for concrete. Marble powder is a limestone origin waste material. Samples 150x150x150 mm and 150x150x450 mm in size were produced. It is known that there is a close relation between concrete compressive strength and fracture parameters. Critical stress intensity factor KIC s and critical crack tip opening displacement CTODc, fracture parameters were determined. Consequently, it was observed that concrete compressive strength and powder admixture are effective on fracture parameters of SCC. © 2013 Sustainable Construction Materials and Technologies. All rights reserved.
3rd International Conference on Sustainable Construction Materials and Technologies, SCMT 2013 -- 18 August 2013 through 21 August 2013 -- Kyoto -- 137587
Keywords: Fracture parameters; Marble powder; Peak load method; Self-compacting concrete